Design of an Axisymmetric Triangular Heatsink with Radial Arrangement: An Experimental Investigation of Natural Convection Heat Transfer - Jamal Bakr Khaleel; Merdin Danışmaz; Tahseen Ahmad Tahseen; Mohammed I. A. Tahseen; Thamer Khalif Salem (Tikrit Journal of Engineering Sciences)
Radial heat sinks are often employed as heat transfer enhancers because they increase the heat transfer surface area. Novel shapes of fins are used to enhance thermal heat performance under free convection heat transfer. The present experimental study investigates a new-fin shape effect on the thermal behavior of a radial heat sink with a circular base. The objective is to select the best reference model by comparing the three heat sink models, I, II, and III. The study was conducted for the heat-supplied rates of 20.16, 66.03, 105.30, 157.62, and 196.08 W. The present results showed that the fin in case I configurations dissipated heat transfer up to 12.07% and 30% compared to cases II and III, respectively, at high Rayleigh numbers. The thermal resistance in case III reduced to 13.91% and 16.23% compared to case I and case II, respectively, at the maximum Rayleigh number value. Then, based on experimental data, a correlation was suggested to estimate the Nusselt number for free convection from radial heat sink with vertically oriented double triangular fins.